Every thing is sacred - Rohr, Richard; Boland, Patrick (Psychotherapist) (Convergent, 2021)
"In this companion to The Universal Christ, Richard Rohr and Patrick Boland offer forty reflections and practices exploring what it means to live "in Christ." In his landmark book The Universal Christ, Richard Rohr articulated a transformative view of what it means to recognize Jesus as "Christ"-as a portrait of God's constant, unfolding work in the world. Now, in partnership with Patrick Boland, a psychotherapist and member of Rohr's Center for Action and Contemplation community, he invites readers to engage with the themes of the book through spiritual practice. Each reflection in this book draws on a key passage of The Universal Christ, paired with prayers, journal prompts, and embodied exercises that invite readers into a more personal encounter with the truth that the presence and compassion of the Christ are in every thing. Whether read daily for the season of Lent or explored over the course of a year, Every Thing Is Sacred is a hope-filled journey into the love at the heart of all things"--